A new genus and species of soft scale insect (Hemiptera: Coccomorpha: Coccidae) on Ficus sp. from Côte d’Ivoire - Hodgson, Chris J. (Zootaxa, 2023)
During a brief visit to the West African Rice Development Association (WARDA) in Bouaké, Côte d’Ivoire, several samples of scale insects (Hemiptera: Coccomorpha) were collected. Amongst these was an undescribed genus and species of soft scale (Coccidae: Coccinae), Bandamacoccus labiosus Hodgson (gen. nov. and sp. nov.). The adult female and second-instar male nymph are described below. A striking feature of both stages is the large size of the labium, which is wider than the clypeolabral shield, whilst the second-instar male also has a prominent inner submarginal band of ventral microducts.